Comparative study of Jabodetabek private companies and government institutions’ work systems effectiveness - Kolifah, Kolifah; Syawaludin, Muhammad Rival; Pasya, Ainun Thoyyibah (Indonesian Journal of Multidisciplinary Science, 2024)
A work system is one of the important aspects that must be owned by private companies or government institutions to regulate and manage the performance of their employees in achieving organizational goals. Private companies and government institutions are two different organizations and of course have different work systems. This encouraged researchers to conduct research with the title comparative study of the effectiveness of the work systems of private companies and government institutions in Jabodetabek. The aim of this research is to compare the effectiveness of work systems between private companies and government institutions in Jabodetabek. The research method used is qualitative with a library approach so that the data collection technique is carried out by collecting various documents that are appropriate to the research focus and then carrying out in-depth analysis. The research results show that the work system of private companies is more effective than that of government institutions. because the scope of work of private companies is smaller than the scope of work of government institutions where regulations or rules are more binding and difficult to change or adapt to needs. If there are regulations that need to be changed, it will take longer, even though currently the government has made various efforts to provide the best performance that is more effective compared to the previous period.